Translation of Qur'anic Verses on Muamalah Study of Lafaz Hakiki And Majazi (Translation of Ministry of Religious Affairs of the Republic of Indonesia) - Siti Nur Rohmah; Imron Rosyadi; Syamsul Hidayat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The Qur'an is a scripture revealed by Allah to the Prophet Muhammad in Arabic very clearly and clearly, which is held as a guide to life by Muslims. The Qur'an has a rich variety of stylistic styles, including the true and majazi styles. True style refers to words that have original meanings as stipulated in the Qur'an. Majazi is the transfer of the basic meaning of a word to another meaning with a specific purpose or reason, or an expansion of the scope of meaning from its original meaning. This research uses librarry research that relies on data from various sources such as books, journals, and books relevant to the research focus and uses descriptive analysis methods, so as to explain clearly about the muamalah verses in the Qur'an, the study of the true lafaz and majazi translation of the Ministry of Religious Affairs of the Republic of Indonesia. This study has conclusions about the theory of translation of the Qur'an, the Verse About Muamalah, the Qur'an provides the basis, principles, laws, and ethics related to muamalah or socioeconomic interaction. The verses of the Qur'an discuss economics, transaction ethics, property, usury, buying and selling, ijarah, accounts receivable, wadi'ah, ariyah, wakalah, kafalah, shirkah, and mudarabah. Understand the difference between lafaz hakiki and majazi and ways to identify them.